Pengaruh Strategi Pemasaran Terhadap Minat Santri Baru Pondok Pesantren Full Day Sunan Ampel Tahun Pembelajaran 2018/2019 - Mamlukhah, Mamlukhah; Suprapto, Ribut; Rohmatillah, Uliya (Jurnal Manajemen Pendidikan Islam Darussalam, 2019)
The purpose of this study is to find out: 1). marketing strategy Full Day Boarding School Sunan Ampel Bangorejo Banyuwangi, 2). interest in new students at Sunan Ampel Bangorejo Banyuwangi Islamic Boarding School Full Day, and 3). the effect of the marketing strategy on the interests of the new students of the Sunan Ampel Bangorejo Banyuwangi Boarding School Full Day. As for sampling using the Slovin formula, this type of research is quantitative with questionnaire data collection methods, observation, documentation. Whereas the validity test uses the Product Moment formula, while the reliability test uses the Cronbach Alpha formula. Then for testing the hypothesis using the T-test and F test and for normality using the classic assumption test. The results of this study indicate, that 1). The marketing strategy of the Sunan Ampel Full Day boarding school is classified as good, 2). the interest of new students at the Sunan Ampel Full Day boarding school is quite good, 3). seen the percentage of the R Square value of 0.733, which means that the marketing strategy (X) has a considerable influence on the interests of new students (Y) of 73.3%, and the remaining 26.7% is influenced by other variables.